The Availability of the Requirements for a Responsibility Accounting System in Local Authorities Operating in the Gaza Strip: A Field Study (Palestine Technical College Journal for Research and Studies, 2019)
This study aims to identify the extent of the application of responsibility accounting system as a tool for monitoring and evaluating the municipalities in the Gaza Strip. In order to achieve this, the study relied on design a questionnaire distributed to a sample of heads of municipalities, directors of departments, accountants and auditors working in large municipalities in category (A). (75) Questionnaire was distributed and the recovery rate was (73.3%). The study reached several conclusions, including: the municipalities have the components of responsibility accounting system, this include existence of a municipal accounting system that meets the needs of the centers of responsibility to enable them to perform their work. Based on the study results, the study reached a set of recommendations, including the need to increase attention to the administrative structure of the municipalities by defining the terms of reference and responsibilities of municipal responsibility.
Keywords: Responsibility Accounting; Control System; Responsibility Centers; Municipalities of the Gaza Strip